2004
DOI: 10.1002/ejoc.200400036
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Dihydropyridines and Nucleophiles with Carbene Complexes of Chromium: Diastereo‐ and Enantioselective Synthesis of Polycyclic Butenolides

Abstract: The interaction of N‐methyldihydropyridine with carbene complexes of chromium promotes their spontaneous homologation upon addition of a hydride to the carbene carbon and an insertion of CO. This is followed in the case of complexes tethered to a triple bond by cascade insertions of the triple bond and of a CO ligand giving finally butenolides. The scope of the reaction has been established with its limitations, together with the stereochemical outcome, which is discussed. [5.5], [5.6], [5.7] bicyclic and tric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 155 publications
1
5
0
Order By: Relevance
“…This result can be rationalized in view of previous observations from this Laboratory [11,12] and from others [13,14]. The addition of nucleophiles to Fischer carbene complexes to give useful functionalized tetrahedral intermediates is now well established: addition of the enolate 4 originating from the ketene acetal and potassium t-butoxide probably led to a potassium (1-alkoxy 3-oxatrimethylsilylcarboxylate)pentacarbonyl tungstate (5).…”
supporting
confidence: 62%
“…This result can be rationalized in view of previous observations from this Laboratory [11,12] and from others [13,14]. The addition of nucleophiles to Fischer carbene complexes to give useful functionalized tetrahedral intermediates is now well established: addition of the enolate 4 originating from the ketene acetal and potassium t-butoxide probably led to a potassium (1-alkoxy 3-oxatrimethylsilylcarboxylate)pentacarbonyl tungstate (5).…”
supporting
confidence: 62%
“…agents, [12][13][14] such compounds could also be used for the biomimetic reduction of Fischer carbene complexes. [15][16][17] The second was the dinucleophilic addition reactions, since we had discovered that bis(trimethylsilyl)ketene acetals 7 constitute an original class of ketene acetals among nucleophiles, [18][19][20][21] as they can behave as 1,3-carbon,oxygen dinucleophiles 8 in one-pot reactions, as the result of successive cleavage of both oxygen-silicon bonds (Scheme 2). pyridines through the use of bis(trimethylsilyl)ketene acetals had not been described to the best of our knowledge, although an early example of the addition of the bis(trimethylsilyl)ketene acetal 7a derived from acetic acid and giving the corresponding ester has been outlined.…”
Section: Introductionmentioning
confidence: 99%
“…For related literature about the cited reactions, see: Bassetti et al (2005); Beck et al (2001); Liu et al (2006); Ma & Gu (2005); Rudler et al (2004).…”
Section: Related Literaturementioning
confidence: 99%
“…A range of synthetic approaches to this class of compounds exists and includes among others, palladium-catalyzed cross-coupling reaction between allenoic acids and 2,3-allenols (Ma et al, 2005), gold-catalyzed Z-enynol cyclization (Liu et al, 2006) or ring-closing metathesis of methallyl acrylates (Bassetti et al, 2005). However, only a few multicomponent methods have been reported that include a Passerini reaction (Beck et al, 2001) and Fischer carbene complexes (Rudler et al, 2004) among others. In this context, a new multicomponent method for the synthesis of bicyclic 2-butenolides through the coupling of imide lithium enolates, propargylic organometallics and Fischer carbene complexes will be soon published elsewhere.…”
Section: Data Collectionmentioning
confidence: 99%